Superior antiviral activity of IFNβ in genital HSV-1 infection - Schmitz, Yasmin; Schwerdtfeger, Mara; Westmeier, Jaana; Littwitz-Salomon, Elisabeth; Alt, Mira; Brochhagen, Leonie; Krawczyk, Adalbert; Sutter, Kathrin (Frontiers in Cellular and Infection Microbiology, 2022)
Type I interferons (IFNs) present the first line of defense against viral infections, providing antiviral, immunomodulatory and antiproliferative effects. The type I IFN family contains 12 IFNα subtypes and IFNβ, and although they share the same receptor, they are classified as non-redundant, capable to induce a variety of different IFN-stimulated genes. However, the biological impact of individual subtypes remains controversial. Recent data propose a subtype-specificity of type I IFNs revealing unique effector functions for different viruses and thus expanding the implications for IFNα-based antiviral immunotherapies. Despite extensive research, drug-resistant infections with herpes simplex virus type 1 (HSV-1), which is the common agent of recurrent orogenital lesions, are still lacking a protective or curing therapeutic. However, due to the risk of generalized infections in immunocompromised hosts as well as the increasing incidence of resistance to conventional antiherpetic agents, HSV infections raise major health concerns. Based on their pleiotropic effector functions, the application of type I IFNs represents a promising approach to inhibit HSV-1 replication, to improve host immunity and to further elucidate their qualitative differences. Here, selective IFNα subtypes and IFNβ were evaluated for their therapeutic potential in genital HSV-1 infections. Respective in vivo studies in mice revealed subtype-specific differences in the reduction of local viral loads. IFNβ had the strongest antiviral efficacy against genital HSV-1 infection in mice, whereas IFNα1, IFNα4, and IFNα11 had no impact on viral loads. Based on flow cytometric analyses of underlying immune responses at local and peripheral sites, these differences could be further assigned to specific modulations of the antiviral immunity early during HSV-1 infection. IFNβ led to enhanced systemic cytokine secretion and elevated cytotoxic responses, which negatively correlated with viral loads in the vaginal tract. These data provide further insights into the diversity of type I IFN effector functions and their impact on the immunological control of HSV-1 infections.